Are political support-driven policies always bad? The case of large interest groups - Gael Lagadec (European Journal of Government and Economics (EJGE), 2014)
The action of active interest groups (lobbies) has been traditionally considered to be a source of harmful waste for the economy which reduces social well-being. Can this analysis be adapted to the case of large unorganised groups which do (Not ask for anything directly? Or, on the contrary, does the setting up of policies which improve the situation of these large groups permit an improvement in social welfare? We start from classical (public choice) analyses of lobbying and rent-seeking developed since the 1970s, closely linked with the hypothesis of re-election-seeking politicians, before extending our analysis also to consider non-sector-specific policies and passive interest groups (notably those too large to meet the Olsonian condition of efficient collective action). Then the research question to be answered becomes whether promoting the interest of large groups can deliver social welfare as defined by the incumbent's social welfare function. We refer to the political cycles' evidence to consider that (No social welfare objective can motivate the favouring of large groups.
Keywords: 330; interest groups; lobbies; collective action; social welfare